2017
DOI: 10.1161/jaha.117.006309
|View full text |Cite
|
Sign up to set email alerts
|

Forward Left Ventricular Ejection Fraction: A Simple Risk Marker in Patients With Primary Mitral Regurgitation

Abstract: BackgroundThe timing of mitral valve surgery in asymptomatic patients with primary mitral regurgitation (MR) is controversial. We hypothesized that the forward left ventricular (LV) ejection fraction (LVEF; ie, LV outflow tract stroke volume divided by LV end‐diastolic volume) is superior to the total LVEF to predict outcomes in MR. The objective of this study was to examine the association between echocardiographic parameters of MR severity and LV function and outcomes in patients with MR.Methods and ResultsT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 42 publications
(109 reference statements)
1
16
0
Order By: Relevance
“…Dupuis et al [33] stated that the forward LVEF (LV outflow tract SV divided by LVEDV) is superior to the total LVEF in predicting outcomes in mitral regurgitation. Other similar studies have described the use of PC-CMR for calculation of the mitral regurgitant volume by subtraction of the aortic forward flow calculated at the aortic root from the total left ventricular stroke volume (LVSV) obtained from planimetry of the LV end-diastolic and end-systolic contours [34].…”
Section: Discussionmentioning
confidence: 99%
“…Dupuis et al [33] stated that the forward LVEF (LV outflow tract SV divided by LVEDV) is superior to the total LVEF in predicting outcomes in mitral regurgitation. Other similar studies have described the use of PC-CMR for calculation of the mitral regurgitant volume by subtraction of the aortic forward flow calculated at the aortic root from the total left ventricular stroke volume (LVSV) obtained from planimetry of the LV end-diastolic and end-systolic contours [34].…”
Section: Discussionmentioning
confidence: 99%
“…Forward LVEF less than 35% has been demonstrated as a cut off value to predict higher short‐term mortality after MV surgery 17 . Therefore, forward LVEF may be a superior parameter to the “total” LVEF and may be employed to predict LV dysfunction after MV surgery 18 . On the other hand, it has been shown that a postoperative (6 months) LVEF less than 50% indicates decreased long‐term survival in patients undergoing surgery for MR 19 .…”
Section: Discussionmentioning
confidence: 99%
“…LVEF and may be employed to predict LV dysfunction after MV surgery. 18 On the other hand, it has been shown that a postoperative…”
Section: Univariable Analysismentioning
confidence: 99%
“…Forward LVEF was calculated using the following equation: forward LVEF = 100 × forward SV/LVEDV, where the forward SV was measured by pulsed wave Doppler in the LV outflow tract [ 14 ]. To determine intra-observer and inter-observer variability, a random sample of 25% of left ventricular outflow tract (LVOT) recordings was submitted twice to the first investigator and once to a second investigator.…”
Section: Methodsmentioning
confidence: 99%
“…Forward LVEF, calculated as forward stroke volume (SV) divided by LV end-diastolic volume (LVEDV), may helpful in stratifying the long-term risk in patients with ≥ mild MR [ 14 ]. Few studies to date have evaluated the ability of forward LVEF to predict short-term risk, especially in terms of LVD after mitral valve surgery.…”
Section: Introductionmentioning
confidence: 99%